Evaluation of acoustic radiation force impulse imaging for the clinicopathological typing of renal fibrosis - CUI, GUANGHE (D.A. Spandidos, 2014)
This study aimed to explore the assessment value of virtual touch quantization (VTQ) for the clinicopathological typing of renal fibrosis. The quantitative detection of 76 patients with nephropathy was performed using acoustic radiation force impulse imaging (ARFI). The extent of the renal fibrosis in each patient was confirmed using ultrasound-guided biopsy pathology. The VTQ values were compared with the degree of renal fibrosis in order to analyze the correlation between them. Patients were divided pathologically into four groups, as follows: non-fibrosis (n=14), mild fibrosis (n=40), moderate fibrosis (n=21) and severe fibrosis (n=1). Compared with the non-fibrosis group, the VTQ values of the mild and moderate fibrosis groups were significantly increased (P<0.01); however, there was no significant difference between the VTQ values of the mild and moderate fibrosis groups (P>0.05). According to the receiver operating characteristic (ROC) curve, a VTQ value of renal parenchyma of >1.67 m/sec was determined to be an indicator of renal fibrosis, with a sensitivity of 86.3% and a specificity of 83.3%. VTQ technology may be significant in the assessment of the extent of renal fibrosis.